Detection of bacillus Galmette-Guérin (Mycobacterium bovis BCG) DNA in urine and blood specimens after intravesical immunotherapy for bladder carcinoma. - Siatelis, Argyrios; Houhoula, Dimitra P; Papaparaskevas, Joseph; Delakas, Dimitrios; Tsakris, Athanassios (J Clin Microbiol, 2011)
A real-time PCR targeting IS6110 was employed for the detection of Mycobacterium tuberculosis DNA in specimens collected from 10 patients treated with intravesical M. bovis bacillus Galmette-Guérin (BCG) immunotherapy for bladder malignancy. BCG DNA was detected in all urine specimens taken 24 h after the instillations, as well as in 24% of the specimens collected 7 days after the instillations; it was also detected in a single specimen taken 6 weeks after the last instillation. BCG DNA was detected in 8.3% of the blood specimens taken 1 day after instillation, and its amplification was associated with cases of self-limiting fever. These findings give indications that this real-time PCR is helpful to recognize BCG bacteremic cases, which may lead to mycobacterial infection.
Keywords: Aged; Aged, 80 and over; Blood; Carcinoma; DEAD-box RNA Helicases; DNA Primers; DNA Transposable Elements; DNA, Bacterial; Female; Humans; Immunotherapy; Male; Middle Aged; Mycobacterium bovis; polymerase chain reaction; Urinary Bladder Neoplasms; Urine